2019
DOI: 10.1128/msphere.00394-18
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evidence for Two Carbon Fixation Pathways (the Calvin-Benson-Bassham Cycle and the Reverse Tricarboxylic Acid Cycle) in Symbiotic and Free-Living Bacteria

Abstract: Primary production on Earth is dependent on autotrophic carbon fixation, which leads to the incorporation of carbon dioxide into biomass. Multiple metabolic pathways have been described for autotrophic carbon fixation, but most autotrophic organisms were assumed to have the genes for only one of these pathways. Our finding of a cultivable bacterium with two carbon fixation pathways in its genome, the rTCA and the CBB cycle, opens the possibility to study the potential benefits of having these two pathways and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 31 publications
5
37
0
Order By: Relevance
“…Furthermore, the known NADH-dependent FRDs are not involved in central energy metabolism, while P. thermosuccinogenes, a strictly anaerobic fermentative organism and likely to be constrained by its ability to generate metabolic energy, produces succinic acid as one of its main products of fermentation. It seems therefore credible that it can couple succinic acid production to additional energy conservation, in the form of reduced Something very similar was proposed recently for the reverse TCA-cycle of sulfur-oxidizing bacteria found in symbiosis with tubeworms (24). In those bacteria, the HdrABC-FlxABCD complex colocalizes on the genome with a FRD (homologous to the methanogenic thiol-driven FRD, TfrAB) as well as a 2oxoglutarate:ferredoxin oxidoreductase (KorABCD).…”
supporting
confidence: 53%
“…Furthermore, the known NADH-dependent FRDs are not involved in central energy metabolism, while P. thermosuccinogenes, a strictly anaerobic fermentative organism and likely to be constrained by its ability to generate metabolic energy, produces succinic acid as one of its main products of fermentation. It seems therefore credible that it can couple succinic acid production to additional energy conservation, in the form of reduced Something very similar was proposed recently for the reverse TCA-cycle of sulfur-oxidizing bacteria found in symbiosis with tubeworms (24). In those bacteria, the HdrABC-FlxABCD complex colocalizes on the genome with a FRD (homologous to the methanogenic thiol-driven FRD, TfrAB) as well as a 2oxoglutarate:ferredoxin oxidoreductase (KorABCD).…”
supporting
confidence: 53%
“…Particularly, gamaproteobacteria with obviously higher percentage (39.88% in S1, 85.91% in S2, 93.56% in S3, and 96.35% in S4) was increased along with culturing, which have been extensively reported that most of this subdivision are capable of photoautotrophic pathway or chemolithoheterotrophic pathway for CO 2 xation [21][22][23][24]. Cyanobacteria, Ignavibacteriae, Chlorobi, and Bacteroidetes were only detected in sample S1, which have been well-elaborated the capacity of CO 2 xation, nitrogen xation, and hydrogen production via photoautotrophy or chemolithoautotrophy, yet the phylum (like Ignavibacteriae, Chlorobi, etc) were sensitive to oxygen [22][23][24][25][26]. Oxygen, possibly generated from the oxygenic photoautotroph like Cyanobacteria, was detected (data shown in Fig.…”
Section: Microbial Diversity and Statistical Analysis Of Protein Catementioning
confidence: 81%
“…S6). Key genes of these completed pathways, namely RubisCO for CBB cycle [23,[27][28][29], ATP citrate lyase for rTCA cycle [22,23,25] and CO dehydrogenase/acetyl-CoA synthase for WL pathway [23,30] were detected and showed the signi cant abundance in all samples ( Fig. 4a), demonstrating that the microbial communities embodied the ability of autotrophic carbon xation.…”
Section: Metabolic Pathways and Key Microorganisms Involved In Carbonmentioning
confidence: 95%
See 1 more Smart Citation
“…These bacteria could be using both cycles depending on the environmental setting, as suggested for the sulfide-oxidizing gammaproteobacterial symbionts of vestimentiferan tubeworms 4648 found at hydrothermal vents, the large sulfur bacteria Beggiatoa and Thiomargarita spp. 4951 , and recently the cultivable sulfur oxidizer Thioflavicoccus mobilis 52 . The tubeworm symbiont Ca.…”
Section: Main Textmentioning
confidence: 99%